Constructing and Researching the Collaborative Cultivation Model of Farmers' Digital Literacy from the Perspective of Activity Theory - Xiaoyu WANG, Shuo LI, Suluo ZHANG (Nongye tushu qingbao xuebao)
[Purpose/Significance] In the context of digital rural development, farmers' digital literacy is greatly influenced by both intrinsic motivations and external influences. Cultivating digital literacy is of great significance in accelerating farmers' integration into the digital process, promoting the construction of digital villages, and facilitating the revitalization of rural talent. As an innovative mechanism for farmer education, the synergistic cultivation of farmers' digital literacy is poised to emerge as a critical research focus in the revitalization of rural talent. [Method/Process] Drawing from activity theory, the static components of this synergistic cultivation - consisting of the interrelated elements of goals, core aspects, and mediating factors - offer a nuanced perspective on the intricacies involved in enhancing farmers' digital literacy. The framework includes production, communication, sharing, and collaboration subsystems that together form a dynamic structure for cultivating farmers' digital literacy. By examining both static activity elements and dynamic operational systems, we conducted an in-depth analysis of the challenges encountered within each subsystem during collaborative cultivation efforts. [Results/Conclusions] We recommend the optimization strategies such as refining the use of tools, improving the regulatory framework, maximizing the potential for collaboration, and establishing sustainable mechanisms. The farmers' digital literacy collaborative cultivation activity model constructed in this paper is based on the background of digital rural construction and high-quality farmer cultivation. With the agricultural broadcasting school (center) as the core subject, it interacts and cooperates with other communities, and through the online digital platform and offline regular practice tools, it realizes the embedding of tool use, the improvement of the rule system, the long-term cooperation of activities, and the close participation and co-construction through the interaction and coordination of the four subsystems of production, sharing, communication and cooperation. It is closer to the digital scene requirements of farmers' cultivation. Moreover, few studies have applied activity theory to the cultivation activities of farmers' digital literacy, and analyzed the interaction and coordination process among elements from a dynamic and holistic perspective. The proposed framework for synergistically cultivating farmers' digital literacy not only provides detailed insights into educational practices, but also offers theoretical foundations for improving practical pathways in this area. The limitation of this article lies in the fact that the collaborative mechanisms and existing problems among the subsystems in the collaborative cultivation model of farmers' digital literacy have not been systematically sorted out. In response to the above limitations, continuous research based on the integration of different perspectives and methods will be conducted on the hot topic of cultivating farmers' digital literacy, which is "always in progress".